Conceptual Model of Teachers’ Work Engagement: A Literature Review [Model Konseptual Keterikatan Kerja Guru: Reviu Literatur] - Soeprapto; Wiwin Hendriani (ANIMA Indonesian Psychological Journal, 2021)
Being a teacher was not as simple as initially thought, not only as a profession but also as a role with great responsibility within. The aim of this study was to construct a conceptual model of teachers’ work engagement in a school setting by reviewing several literatures. The articles were obtained from three journal databases, namely: (1) Science Direct; (2) Springer Link; (3) and Portal Garuda, with the limitation of being published in the recent 10 years of the time of this study (2009 - 2019). The initial search resulted in 789 articles which were then selected by using inclusion and exclusion criteria to obtain four articles (N = 4) employing quantitative approach as the final result. Based on the review, several variables had significant correlation to teachers’ work engagement. These variables were then grouped as antecedent and consequence variables. The conceptual model of teachers’ work engagement in this study was expected to be beneficial as consideration in managing education. Menjadi seorang guru tidak semudah yang dibayangkan, tidak hanya sebagai sebuah profesi tetapi juga sebagai suatu peran yang mengemban tanggung jawab yang besar. Studi ini bertujuan untuk mendapatkan gambaran model konseptual work engagement pada guru dalam situasi sekolah dengan menelaah sejumlah literatur. Adapun jurnal yang digunakan dalam studi ini dikumpulkan melalui tiga pangkalan data jurnal, yaitu: (1) Science Direct; (2) Springer Link; dan (3) Portal Garuda, dengan batasan penerbitan 10 tahun terakhir waktu pelaksanaan studi ini (2009 - 2019). Hasil pencarian awal menemukan 789 artikel yang selanjutnya diseleksi melalui kriteria inklusi dan eksklusi sehingga diperoleh empat artikel (N = 4) yang semuanya berlandaskan pendekatan kuantitatif. Hasil telaah mengungkap sejumlah variabel yang memiliki hubungan yang signifikan terhadap work engagement guru. Selanjutnya, sejumlah variabel ini digolongkan sebagai antecedent variables dan consequence variables. Model konseptual work engagement guru ini diharapkan dapat menjadi pertimbangan dalam pengelolaan pendidikan.